Multicollinearity in Tourism Demand Model : Evidence from Indonesia - Wasiaturrahma, Dr (Universitas Negeri Semarang, 2021)
The demand for tourism in Indonesia continues to increase every year but cannot reach the predetermined target. Studies on tourism demand have been done a lot, especially in Indonesia.The selection of the dependent variable in tourism demand is not problematic and acceptable, however, the selection of the independent variable is still unclear. This study aims to provide an appropriate Indonesian tourism demand model and analyze the determinants of tourism demand in Indonesia. The estimation technique used is a static panel regression. The results of this study prove that there is multicollinearity in the tourism demand model when exchange rate and relative price are combined into one model, showing that relative price are good proxies in representing tourism price, and showing that substitution price are the main determinants of tourism demand in Indonesia. The policy implications recommended in this study are monitoring the economic growth of the origin countries of most tourists visiting Indonesia, improving the qual ity of Indonesian tourism, and developing the Wonderful Indonesia program.